A Study on the Effectiveness of Social Security System for the Fisher Folks in Mangaluru - Pradeep M. D., (International Journal of Management, Technology and Social Sciences (IJMTS), 2018)
Unorganised sector occupies a predominant portion in the workforce of India. The work is considered to be the physical and mental engagement by human beings for economic productivity. Fisheries Sector has become a source ofincome and employment to those who engage in unorganised employments for their life. India is the second largest producer of fish in the world by contributing 5.68 per cent of global fish production and second largest producer of fish by aquaculture after China. In the National Fish Productivity, State of Karnataka contributes almost 5.8 per cent securing 6th Position in marine productivity and 9th position in the inland fish productivity. Fisheries sector has enriched its share in the national development after effective usage of technology to increase yield per area of water thereby earning more foreign exchange. Fishing occupation is normally hazardous causing harm to the health of the fisher folks. It is essential to provide Social security protections to the fisher folks against contingencies including disability, sickness, employment injuries, occupational diseases and unemployment. The maximum welfare to the fisher folks can be assured only through the execution of Comprehensive Social Security Policy linking Social Assistance Programmes and Social Security Schemes. This study is descriptive and analytical in nature. The study results analyse the implications of social security measures among the fisher folks living in the ThotaBengre fishing village of Mangaluru Taluk in Dakshina Kannada District of Karnataka State in India. The study review upon the implications of various social security schemes offered to the fishermen in terms of its coverage and benefit. A good attempt is also made to identify the level of awareness among the fisher folks about social security schemes provided by the government at Centre and State levels respectively. This paper suggests measures for the legislators and fisheries department to improve the benefit schemes thereby securing the inclusive growth of the fishing community.